Personality Classification Of Social Media Users Based On Type Of Work And Interest In Information - Rizky Yudha Pratama; Sri Suryani Prasetyowati; Yuliant Sibaroni (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
Social media is a platform that makes it easier for users to interact and get to know each other because in social media there are profiles, statuses, and user uploads. Therefore, many studies utilize social media because there is much information that can be explored on social media, one of which is research on the personality classification of social media users. However, many studies related to personality classification of social media users have failed due to too many model target classes, which result in low accuracy. In this research, the author uses the Myers-Briggs Type Indicator (MBTI) model, which is focused on only two personality classes, namely "Introvert/Extrovert" and "Sensor/Intuitive" with the features type of work and interest in information which are feature representations of the personality class used to reduce the target class. The best accuracy result is 95.87% after classifying using two personality classes.